Simulação de um inversor de frequência para acionamento de motores de indução trifásicos em um sistema de ar condicionado para ônibus híbridos elétricos - Abente, Fabrizio José María Ardissone (2016)
Hybrid buses are a reality for transportation of public in urban land. The air conditioning compressor drive should be independent of the diesel engine being or not running. For this system to work efficiently, this study proposes to set the logic and mode of operation of the inverter, model it and simulate it, transfer the model generated to a FPGA using automatic code generation and finally, check the good transfer of this model. For this purpose, there were intense bibliographic research and a model of the operation of the inverter was done and simulated using Matlab Simulink HDL Coder module software and the transfer of this model to an FPGA was performed; The simulations, the modeling, the transfer of the auto generated code and the tests performed were successful in using this technique to develop an inverter to drive the air conditioning compressor for hybrid electric vehicle.